Pengaruh Pengetahuan Wajib Pajak, Kesadaran Wajib Pajak, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Utami Widya Karlina; Mukhlizul Hamdi Ethika (Jurnal Kajian Akuntansi dan Auditing, 2020)
This study aims to prove the effect of knowledge, awareness and tax sanctions on vehicle taxpayer compliance in Kabupaten Kerinci and Sungai Penuh City. Respondents who participated in this study were 100 respondents and the samples were taken using accidental sampling method. The data was collected using a questionnaire and the data was tested using descriptive statistical analysis, validity and reliability tests, classical assumption tests and multiple linear regression analysis. The test results show that knowledge and awareness of taxpayers have a positive effect on tax compliance, while tax sanctions have no effect on vehicle taxpayer compliance.